INDONESIA'S ECONOMIC INTEREST IN BRICS MEMBERSHIP IN 2018-2025 - Izqi Aina Fatiah; Khoirunnisa Khoirunnisa (Pojok Publisher, 2026)
This study examines Indonesia’s economic interests in its decision to become a full member of BRICS in 2025, focusing on the period from 2018 to 2025. Indonesia’s membership in this alliance is influenced by global dynamics that reveal the limitations of the international economic order, which developed countries have dominated. This study aims to identify Indonesia’s strategic motivations in the context of economic diplomacy and how the government uses the BRICS forum to pursue its national interests. This study uses a descriptive qualitative approach through a literature review and analyzes the cooperation and negotiation processes carried out by Indonesia. Economic diplomacy theory is the primary framework for explaining how states combine political and economic instruments to achieve national prosperity and strategic stability, supported by the concepts of national interests, cooperation, and negotiation. The findings reveal that Indonesia uses BRICS as an alternative financing channel for development, export market diversification, and strengthening its bargaining position in global forums. However, this membership also presents challenges, such as the dominance of major powers within BRICS, potential tensions with regional organizations, and risks associated with foreign debt management. The main contribution of this study is a comprehensive analysis of Indonesia’s economic diplomacy strategy within the context of South-South cooperation, which has not been extensively examined in previous research.